An investigation of the crash performance of magnesium, aluminum and advanced high strength steels and different cross-sections for vehicle thin walled energy absorbers - Demirci, Emre; Yildiz, Ali Riza (Carl Hanser Verlag, 2018)
In this paper, the effect of conventional steel, new generation DP-TRIP steels, AA7108 - AA7003 aluminum alloys, AM60 - AZ31 magnesium alloys and crash-box cross-sections on crash performance of thin-walled energy absorbers are investigated numerically for the lightweight design of vehicle structures. According to finite element analysis results, crash performance parameters such as total energy absorption, specific energy absorption, reaction forces and crush force efficiencies are compared for the above-mentioned materials. The energy absorption capability of steel energy absorbers is better than that of aluminum and magnesium absorbers. On the other hand, the energy absorption capacity per unit mass of energy absorbers made from lightweight materials is higher than that of steel energy absorbers. This advantage of lightweight alloys encourages automobile manufacturers to use them in designing structural vehicle components.
Keywords: Crash analysis; lightweight vehicle design; lightweight alloys; new generation steels; crashworthiness